Floral biology and pollination mechanism of Salacca vermicularis Becc. (Areceae: Calameae) - Ng, W. S.; Wong, Sin Yeng (Forest Research Institute Malaysia, 2025)
Salacca (Arecaceae), a genus of palms with 23 accepted species, has its centre of diversity in Borneo. Salacca vermicularis Becc. which is endemic to Borneo, has, despite its edible fruits, has never been studied concerning its floral biology and pollination mechanisms. In this study, the phenology, floral rewards, floral visitors, and possible seed dispersal agents of S. vermicularis were investigated, and experiments performed on the breeding mechanisms of S. vermicularis. Anthesis in staminate flowers begins around noon and persists until early morning on the second day whilst anthesis in pistillate flowers begins around evening and may take up to 40 hours to fully bloom. Floral scent was present throughout the anthesis for staminate and pistillate plants. Apomixis is not present in this species. Several insect visitors were observed, namely Heterotrigona (Apidae) sp. as well as members of Curculionidae, Sciaridae, Formicidae, and Acaridae. Three species of visitors are likely the dispersal agents of S. vermicularis, namely Hystrix sp. (Hystricidae: Hystricinae), Tragulus sp. (Tragulidae) and Lariscus insignis (Sciuridae: Callosciurinae). A mongoose (Herspetidae) was observed foraging nearby but is unlikely as a dispersal agent.